Effects of the addition of edible polysaccharides on the properties of soybean protein isolate gels - Bi, Chonghao; Qie, Aoxue; Wang, Xueying; Zhou, Tong; Chi, Shangyi; Liu, Yi; Tian, Bin (International Journal of Agricultural and Biological Engineering, 2024)
The gel properties of soybean isolate protein (SPI) gels are susceptible to the influence of other components in food products, particularly edible polysaccharides. Therefore, six common edible polysaccharides were selected in this study to investigate their effects on the rheological properties, thermal properties, and microstructure of acid-induced soybean isolate protein self-assembled gels (SPIASG). The experimental results showed that the support capacity and creep recovery of SPIASG with added polysaccharides were higher than those of the control group without added polysaccharides, and the gel with Xanthan gum (XG) was the most effective. The hybrid gel, with added Condensed resin (CR), Xanthan gum (XG), Carrageenan (CA), and CMC formed a stronger network structure. Additionally, compared with SPIASG, the hybrid gel with added edible polysaccharides the water-holding capacity of SPI hybrid gels was relatively improved. In this study, a simple and easy method was obtained to significantly improve the gel properties of SPIASG, analyzed and compared the effectiveness of various polysaccharides to enhance its gel properties, and provided some ideas to improve the gel properties of SPI protein gels. Keywords: soybean protein isolate gels, self-assembled gels, edible polysaccharides, rheological properties DOI: 10.25165/j.ijabe.20241703.8030 Citation: Bi C H, Qie A X, Wang X Y, Zhou T, Chi S Y, Liu Y, et al. Effects of the addition of edible polysaccharides on the properties of soybean protein isolate gels. Int J Agric & Biol Eng, 2024; 17(3): 241-248.